2016
DOI: 10.1093/brain/awv394
|View full text |Cite
|
Sign up to set email alerts
|

Mapping neuroplastic potential in brain-damaged patients

Abstract: It is increasingly acknowledged that the brain is highly plastic. However, the anatomic factors governing the potential for neuroplasticity have hardly been investigated. To bridge this knowledge gap, we generated a probabilistic atlas of functional plasticity derived from both anatomic magnetic resonance imaging results and intraoperative mapping data on 231 patients having undergone surgery for diffuse, low-grade glioma. The atlas includes detailed level of confidence information and is supplemented with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
173
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(204 citation statements)
references
References 76 publications
10
173
0
3
Order By: Relevance
“…Accordingly, in the grid walk task we found that the recovery of motor function of affected limbs in CNF1-treated animals is accompanied by a slight improvement of the performance with unaffected limbs. Since CNF1 promotes activity-dependent plasticity in the adult cortex [15], the toxin might enhance the spontaneous remapping of motor maps in peritumoral areas [26, 27] thus leading to greater functional preservation. Moreover, CNF1 infusion induced a significant increase of PSD95 protein levels in the peritumoral area.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in the grid walk task we found that the recovery of motor function of affected limbs in CNF1-treated animals is accompanied by a slight improvement of the performance with unaffected limbs. Since CNF1 promotes activity-dependent plasticity in the adult cortex [15], the toxin might enhance the spontaneous remapping of motor maps in peritumoral areas [26, 27] thus leading to greater functional preservation. Moreover, CNF1 infusion induced a significant increase of PSD95 protein levels in the peritumoral area.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been a fundamental issue in clinical neuro-oncology to explore the pattern of functional and structural reorganization of the brain following tumor growth (Duffau, 2014;Herbet, Maheu, Costi, Lafargue, & Duffau, 2016;Kinno, Ohta, Muragaki, Maruyama, & Sakai, 2014). Such kind of research holds vital clinical significance in either facilitating the understanding of disease-specific mechanisms in the development and prognosis of diseases, or providing new insight into therapeutic targets for novel and more effective treatment interventions.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible in this case (P4) that, due to fast tumor growth, mainly suppression of functional areas occurs, whereas the integrity of white matter bundles associated with function remains intact. Herbet et al [28] showed via a probabilistic atlas that reorganization at subcortical level, in proximity to white matter tracts, could be less optimal than at cortical level. In addition, Trinh et al [29] demonstrated that a subcortical injury was an independent predictor for longer-term neurological impairments underlining the importance of preservation of subcortical tracts.…”
Section: Discussionmentioning
confidence: 99%